2015
DOI: 10.1063/1.4921127
|View full text |Cite
|
Sign up to set email alerts
|

On the importance of collective excitations for thermal transport in graphene

Abstract: We use equilibrium molecular dynamics (MD) simulations to study heat transport in bulk singlelayer graphene. Through a modal analysis of the MD trajectories employing a time-domain formulation, we find that collective excitations involving flexural acoustic (ZA) phonons, which have been neglected in the previous MD studies, actually dominate the heat flow, generating as much as 78% of the flux. These collective excitations are, however, much less significant if the atomic displacements are constrained in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 33 publications
1
20
1
Order By: Relevance
“…Mode-coupling theory [6] predicts a divergent t −1 scaling of the HCACF for strictly 2D systems and a convergent t for the out-of-plane component, which means that both components eventually saturate and κ for pristine graphene is finite, in agreement with several recent theoretical studies using other approaches [10][11][12][13]34,42], although it is found experimentally that κ is still increasing up to 9 microns [9]. Our results show clearly that the slow convergence of the thermal conductivity is due to the flexural phonons: The convergence of κ out (t) takes a few ns, while κ in (t) converges within a few hundred ps.…”
Section: A Thermal Conductivity Components In Pristine Graphenesupporting
confidence: 70%
See 1 more Smart Citation
“…Mode-coupling theory [6] predicts a divergent t −1 scaling of the HCACF for strictly 2D systems and a convergent t for the out-of-plane component, which means that both components eventually saturate and κ for pristine graphene is finite, in agreement with several recent theoretical studies using other approaches [10][11][12][13]34,42], although it is found experimentally that κ is still increasing up to 9 microns [9]. Our results show clearly that the slow convergence of the thermal conductivity is due to the flexural phonons: The convergence of κ out (t) takes a few ns, while κ in (t) converges within a few hundred ps.…”
Section: A Thermal Conductivity Components In Pristine Graphenesupporting
confidence: 70%
“…Apart from holding great prospects for thermal management applications in nanoelectronic devices, graphene also serves as a benchmark for investigating fundamental questions regarding thermal transport in lowdimensional systems. Anomalous thermal transport, such as logarithmic divergence of thermal conductivity with respect to system size, has been long predicted for 2D lattice models [6][7][8] and it has been debated whether or not this divergence can occur in graphene [9][10][11][12][13]. It has also been predicted that hydrodynamic phonon transport can occur in graphene in a much wider temperature range than in three-dimensional (3D) materials [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…From the review of these theoretical and computational results we can conclude that the studies, independend MD studies, predicting larger contribution to TC from the in-plane acoustic phonons [133,138,144]. However, other MD studies demonstrate opposite view [158,[161][162]. Including collective excitations in the thermal transport models significantly change the final concluions [132,[161][162].…”
Section: <Figure 14>mentioning
confidence: 84%
“…The decrease of the contribution of ZA modes in defected graphene was explained by the breakdown of reflection symmetry in the direction perpendicular to graphene layer [138]. At the same time, Gill-Comeau and Levis [161][162], considering the collective phonon excitations in graphene, concluded that ZA phonons dominate the thermal transport, carrying ~ 78 % of heat. Figure 14 illustrate how sensitive the relative contribution of each phonon polarization branch can be to the amount and nature of the defects in graphene.…”
Section: Ii3 Contribution Of Different Phonon Branches To Thermal Cmentioning
confidence: 96%
See 1 more Smart Citation